Effect of temperature on sulfonamide antibiotics degradation, and on antibiotic resistance determinants and hosts in animal manures - Lin, Hui; Zhang, Jin; Chen, Hongjin; Wang, Jianmei; Sun, Wanchun; Zhang, Xin; Yang, Yuyi; Wang, Qiang; Ma, Junwei (The Science of the total environment, 2017)
Animal manure is a main reservoir of antibiotic residues and antibiotic resistance. Here, the effect of temperature on sulfonamide antibiotics (SAs), sulfonamide-resistant (SR) genes/bacteria was investigated by aerobically incubating swine and chicken manures at different temperatures. In swine manure, the SAs concentration declined with increasing temperature, with a minimum at 60°C. In chicken manure, the greatest degradation of SAs was noted at 30°C. The reduction of relative abundance of antibiotic resistance genes (ARGs) and sul-positive hosts in swine manure was more pronounced during thermophilic than mesospheric incubation; neither temperature conditions effectively reduced these parameters in chicken manure. The relationship between the residual levels/distribution profiles of SAs, ARGs (sul1, sul2 and intI1), cultivable SR bacteria and sul-positive hosts was further established. The antibiotic residual profile, rather than antibiotic concentration, acted as an important factor in the prevalence of ARGs and sul-positive hosts in manure. Corynebacterium and Leucobacter from the phylum Actinobacteria tend to be main carriers of sul1 and intI1; the relative abundance of sul2 was significantly correlated with the relative abundance of cultivable SR bacteria. Overall, differences in resistant bacterial communities also constitute a dominant factor affecting ARG variation. This study contributes to management options for reducing the pollution of antibiotics and antibiotic resistance within manure. [Display omitted] •Temperature response of sulfonamide resistance in manure during aerobic incubation•The effect of temperature on SAs and SR gene/bacteria vary with manure types•Thermophilic removal of SAs and SR genes/bacteria is only evident in swine manure•The antibiotic residual profile affects the prevalence of SR genes/bacteria in manure•Differences in SR bacterial communities influence temperature responses of ARGs